Dynamic Contrast-Enhanced CT Characterization of Xp11.2 Translocation/TFE3 Gene Fusions versus Papillary Renal Cell Carcinomas - He, Jian (Biomed Res Int, 2015)
Purpose. To compare the differences of CT characteristics between renal cell carcinomas (RCCs) associated with Xp11.2 translocation/TFE3 gene fusions (Xp11.2 RCCs) and papillary cell renal cell carcinomas (PRCCs). Methods. CT images and clinical records of 64 patients (25 Xp11.2 RCCs, 15 type 1 and 24 type 2 PRCCs) were analyzed and compared retrospectively. Results. Xp11.2 RCC more frequently affected young (30.7 ± 8.7 years) women (16/25, 64%) with gross hematuria (12/25, 48%), while PRCC more frequently involved middle-aged (54.8 ± 11.1 years) men (28/39, 71.8%) asymptomatically. Xp11.2 RCC tended to be heterogeneous density with some showing circular calcification. Lesion sizes of Xp11.2 RCC (5.4 ± 2.2 cm) and type 2 PRCC (5.7 ± 2.5 cm) were significantly larger than that of type 1 PRCC (3.8 ± 1.8 cm). Xp11.2 RCC contained more cystic components (22/25, 88%) than type 1 PRCC (all solid) and type 2 PRCC (9/24, 36.0%). Type 1 PRCC (13/15, 86.7%) and Xp11.2 RCC (21/25, 84.0%) showed more clear boundary than type 2 PRCC (12/24, 50.0%). Conclusion. CT features including diameter, boundary, attenuation, nature, and circular calcification of the tumor, combined with demographic information and symptoms, may be useful to differentiate Xp11.2 RCC from different subtypes of PRCC.